Engineered cytokine/antibody fusion proteins improve IL-2 delivery to pro-inflammatory cells and promote antitumor activity - Leonard, Elissa K; Tomala, Jakub; Gould, Joseph R; Leff, Michael I; Lin, Jian-Xin; Li, Peng; Porter, Mitchell J; Johansen, Eric R; Thompson, Ladaisha; Cao, Shanelle D; Hou, Shenda; Henclova, Tereza; et al. (JCI insight, 2024)
Progress in cytokine engineering is driving therapeutic translation by overcoming these proteins' limitations as drugs. The IL-2 cytokine is a promising immune stimulant for cancer treatment but is limited by its concurrent activation of both pro-inflammatory immune effector cells and antiinflammatory regulatory T cells, toxicity at high doses, and short serum half-life. One approach to improve the selectivity, safety, and longevity of IL-2 is complexing with anti-IL-2 antibodies that bias the cytokine toward immune effector cell activation. Although this strategy shows potential in preclinical models, clinical translation of a cytokine/antibody complex is complicated by challenges in formulating a multiprotein drug and concerns regarding complex stability. Here, we introduced a versatile approach to designing intramolecularly assembled single-agent fusion proteins (immunocytokines, ICs) comprising IL-2 and a biasing anti-IL-2 antibody that directs the cytokine toward immune effector cells. We optimized IC construction and engineered the cytokine/antibody affinity to improve immune bias. We demonstrated that our IC preferentially activates and expands immune effector cells, leading to superior antitumor activity compared with natural IL-2, both alone and combined with immune checkpoint inhibitors. Moreover, therapeutic efficacy was observed without inducing toxicity. This work presents a roadmap for the design and translation of cytokine/antibody fusion proteins.
Keywords: Recombinant Fusion Proteins; proteinové inženýrství; Neoplasms; Therapeutics; Cell Line, Tumor; Interleukin-2; regulační T-lymfocyty; cytokiny; Drug therapy; Protein Engineering; rekombinantní fúzní proteiny; Immunology; T-Lymphocytes, Regulatory; Animals; lidé; interleukin-2; ženské pohlaví; Humans; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; nádory; Cytokines; nádorové buněčné linie; Mice; Female; Cancer immunotherapy